HISTORICAL AND PHILOSOPHICAL ASPECTS OF THE FORMATION OF PHYSICAL CULTURE AND SPORTS - Polishchuk, Rostyslav (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The study of the history of sport can form an idea of social change and the nature of the sport itself, as it promotes the development of basic human skills. As we delve into history, there is less and less evidence, which complicates the possibility of a reliable theory of the origins and goals of sport. The aim and tasks. The article raises the problem of the general trends in the history of physical culture and sports. The research methodology was determined in the process of analyzing the works of domestic and foreign experts. The methodological basis of the study is the principles of unity of historical and logical, determinism, system, and integrity, etc. The chosen methods are recognized structural-functional approach, comparative and systematic analysis, analytical-descriptive and hermeneutic and general scientific methods. Research results. In particular, as a study result, five theories have been identified: game theory; theory of excess biological energy; theory of war; labor theory; theory of initiation/magic. The author expresses the opinion that there is no importance which theory should take the first place from the philosophical and cultural approach used in the study. The article uses a differentiated analytical approach, which allows us to hypothesize that these theories should not be considered as separate, but in the aggregate of their interaction. Discussion. Each of the theories has its supporters. The preference depends on the cultural-historical conditions the analysis of physical culture and sports is held in. Conclusion. The roots of physical culture and sports, which date back to the ancient world, are outlined. It is noted that the brightest description of sports competitions and traditions in the field of physical education and sports dates from Ancient Greece. It is emphasized that it was Ancient Greece, the "foundation of Europe", some certain concepts related to "sports competitions" arose in. All of them contributed to philosophical thinking, bringing the concepts of "agonism", "aconite", "arete", "echeheria", "kalokagatia" and the phenomenon of "heroization".